ANALISIS PEMBUKTIAN TERHADAP TINDAK PIDANA PENGHINAAN DALAM KONTEN YOUTUBE PADA PUTUSAN PENGADILAN JAKARTA SELATAN (STUDI KASUS PUTUSAN NOMOR 1327/PID.SUS/2019/PN JKT.SEL) - Rizky Setiawan; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2022)
The use of Youtube social media is often misused for purposes that violate the law or unwittingly thecontent uploaded contains criminal acts. One of these cases is Decision Number1327/Pid.Sus/2019/Pn Jkt.Sel or more virally known as the